2021
DOI: 10.1007/s10965-021-02763-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium polyphosphate/cobalt phytate system on flame retardancy and smoke & toxicity suppression of rigid polyurethane foam composites

Abstract: Rigid polyurethane foam/ammonium polyphosphate/cobalt phytate (RPUF/APP/PA-Co) composites were prepared by one-step water-blown method using ammonium polyphosphate (APP)/cobalt phytate (PA-Co) as a flame retardant system. The char residue of RPUF/APP/PA-Co increased significantly than that of RPUF, indicating that the thermal stability of composites was enhanced. Cone calorimetry and smoke density tests showed that when 40 phr APP and 10 phr PA-Co were added, the total heat release and smoke release of RPUF/AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In order to create rigid polyurethane foam/ammonium polyphosphate/cobalt phytate (RPUF/APP/PA‐Co) composites, Zhang et al employed ammonium polyphosphate (APP)/cobalt phytate (PA‐Co) as a flame retardant system. The findings demonstrated the value of APP/PA‐Co loading in producing a thick carbon layer with a high degree of graphitization, which lowered the release of combustibles and smoke from the composite 7 . Aluminum phytate (PA‐Al) and iron phytate (PA‐Fe), which were added to RPUF as flame retardants, were researched by Yang et al for their synthesis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to create rigid polyurethane foam/ammonium polyphosphate/cobalt phytate (RPUF/APP/PA‐Co) composites, Zhang et al employed ammonium polyphosphate (APP)/cobalt phytate (PA‐Co) as a flame retardant system. The findings demonstrated the value of APP/PA‐Co loading in producing a thick carbon layer with a high degree of graphitization, which lowered the release of combustibles and smoke from the composite 7 . Aluminum phytate (PA‐Al) and iron phytate (PA‐Fe), which were added to RPUF as flame retardants, were researched by Yang et al for their synthesis.…”
Section: Introductionmentioning
confidence: 98%
“…The findings demonstrated the value of APP/PA-Co loading in producing a thick carbon layer with a high degree of graphitization, which lowered the release of combustibles and smoke from the composite. 7 Aluminum phytate (PA-Al) and iron phytate (PA-Fe), which were added to RPUF as flame retardants, were researched by Yang et al for their synthesis. The findings showed that RPUF/PA-Fe30 had a much larger char residue than RPUF (12.4 wt %), with a value of 22.1 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other inorganic flame retardants, how to raise the efficiency of APP in flame-retardant EP composites attracts the researchers’ attention. Recently, inspired by synergistic charring catalysis effect, plenty of work on the incorporation of APP and metal elements has been done, for instance, APP and/or iron, zirconium, zinc, aluminum, cobalt, nickel elements, etc. Our previous work also illustrates that the iron-modified APP can both obviously decrease the heat release and diminish the smoke product of EP .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other inorganic ame retardants, how to raise the e ciency of APP in ame retardant EP composites attracts the researchers' attention. Recently, inspired by synergistic charring catalysis effect, plenty of work on the incorporation of APP and metal elements has been done, for instance, APP and/or iron, [21] zirconium, [22] zinc, [23] aluminum, [24] cobalt, [25] nickel elements, [26] etc. Our previous work also illustrates that the iron-modi ed APP can both obviously decrease the heat release and diminish the smoke product of EP.…”
Section: Introductionmentioning
confidence: 99%